Assessment and analysis of accounting and finance apps in start-ups in Germany: an explorative study - Salvy Goel; Claudia Nelly Berrones-Flemmig (IU Internationale Hochschule, 2022)
Small and medium-sized enterprises face several challenges mainly related with lack of access to Finance frequently due to a lack of formal Accounting system and financial management, which leads to weaknesses in their internal financial capabilities. Moreover, from the supply side traditional financial institutions have failed to fulfil the needs of SMEs and presently FinTechs have developed innovative ways to increase the financial literacy in SMEs and to facilitate financing for SMEs (Imanbaeva et al., 2017). This study aims to assess and analyze one of these innovative financial instruments in an explorative way: some relevant Accounting and Finance applications present in the market, based on criteria decided by exploring the scientific literature and evaluating it by interviewing Accounting professionals working in start-ups in Germany. The results show that Zoho Books and Xero turned out to be better than the others in the services provided by them and they received the best ratings and feedback. Their best features are their user friendliness, the integrations offered by them, the diversity of the financial reports that they offer and amount of automation they offer to perform the everyday tasks. The most important factor when choosing an Accounting system is assessing the needs and requirements of the business and then to select the software that best suits the needs. Therefore, this research can be also helpful for small and medium business owners who do not have much idea about the financial aspects and need help with choosing the right accounting software for their business, based on the experience and perspectives of the interviewing Accounting professionals. It can act as a guide for them to understand which factors they should take into account while making their decision and the feedback from the participants can help them while choosing among the five software analysed during this research.
urn:nbn:de:101:1-2022020315302107470412
Keywords: M; O; 650; SME Finance; Fintech; Accounting and Finance apps; innovative financial instruments; start-ups; Germany